2015
DOI: 10.1002/cpp.1969
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive–Behavioural Therapy and Psychodynamic Psychotherapy in the Treatment of Combat‐Related Post‐Traumatic Stress Disorder: A Comparative Effectiveness Study

Abstract: Both cognitive-behavioural therapy and psychodynamic psychotherapy have to be treatments offered in clinics for treating PTSD. Therapists who treat PTSD should be familiar with cognitive-behavioural and dynamic methods. The type of treatment chosen should be based on thorough psychosocial assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 31 publications
(48 reference statements)
0
36
0
6
Order By: Relevance
“…It should be indicated that an applicant who exhibits symptoms of an acute stress response or an acute stress disorder, which occur during the first month of exposure to the event, will always be treated with a behavioural-cognitive orientation. 1 As a rule, cognitive-behavioural therapy is directed to cases in which the applicant evaluates the traumatic event as so severe that he develops negative beliefs, such as: "it is not safe anywhere", "the next disaster will strike soon", "I am dead inside", or "I'm going mad", which lead to dysfunction. Because of these negative beliefs, the traumatic experience is not internalized in the applicant's autobiographic memory, thus adding to the dysfunction.…”
Section: The Decision-making Process At the Staff Meetingmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be indicated that an applicant who exhibits symptoms of an acute stress response or an acute stress disorder, which occur during the first month of exposure to the event, will always be treated with a behavioural-cognitive orientation. 1 As a rule, cognitive-behavioural therapy is directed to cases in which the applicant evaluates the traumatic event as so severe that he develops negative beliefs, such as: "it is not safe anywhere", "the next disaster will strike soon", "I am dead inside", or "I'm going mad", which lead to dysfunction. Because of these negative beliefs, the traumatic experience is not internalized in the applicant's autobiographic memory, thus adding to the dysfunction.…”
Section: The Decision-making Process At the Staff Meetingmentioning
confidence: 99%
“…1 Since the First Lebanon War, the status of the UTC-PTSD has become established as a therapeutic unit that specializes in psychiatric and psycho-therapeutic treatment of chronic PTSD victims, 2 combat stress response victims 3 and acute distress disorder (ADS) victims, as well as in preventive activity in these three fields. 4 Admission for treatment in each of these cases is carried out by indepth psycho-sociological interview, a process which in professional jargon is called "intake."…”
Section: Introductionmentioning
confidence: 99%
“…As modalidades de psicoterapia avaliadas foram: psicoterapia psicodinâmica -PP (Lilliengren et al, 2015;Berghout e Zevalkink, 2009); psicoterapia psicodinâmica de curto prazo -PPCP (Leichsenring et al, 2014;Amianto et al, 2011); psicoterapia psicodinâ-mica de longo prazo -PPLP (Leichsenring et al, 2014;Arvidsson et al, 2011); psicoterapia psicodinâmica intensiva e curto prazo -PPI-CP (Solbakken e Abbass, 2015); psicoterapia psicodinâmica intensiva -PPI (Abass et al, 2015); psicoterapia psicodinâmica de apoio -PPA (Driessen et al, 2013); psicoterapia psicodinâmica breve -PPB (Amianto et al, 2011); psicoterapia psicodinâmica focal -PPF (Zipfel et al, 2014); tratamento comunitário de foco psicodinâmico -TCFP (Vinnars et al, 2009); psicoterapia psicodinâmica interpessoal -PIT (Sattel et al, 2012); psicoterapia psicodinâmica pela internet -PPIN (Johansson et al, 2013); psicanálise -PA (Grande et al, 2009); psicaná-lise com predomínio de interpretações transferências -PAT e sem interpretações transferenciais -PAST (Høglend et al, 2008) e terapia cognitivo comportamental -TCC; (Levi et al, 2015;Zipfel et al, 2014); terapia cognitivo comportamental pela internet -TCCI (Johansson et al, 2013); terapia do esquema -TE (Gude e Hoffart., 2008); terapia de apoio -TA (Vinnars et al, 2009); e, terapia focal -TF (Heinonen et al, 2012). Foram encontradas também intervenções com medicamentos como a fluoxetina (Sørensen et al, 2011), sozinhos ou combinados com psicoterapia psicodinâmica (Koppers et al, 2011); e também intervenções combinadas com outros tratamentos multidisciplinares, tais como dieta alimentar e acompanhamento familiar (Abba-te Daga et al, 2015).…”
Section: Modalidades De Psicoterapiaunclassified
“…Os pacientes eram contatados através de telefone (Levi et al, 2015), e-mail (Marttunen et al, 2008) ou carta (Sattel et al, 2012) para retornarem ao local do atendimento. Em alguns estudos, quando havia dificuldade para o paciente realizar esta etapa da avaliação, os testes eram enviados e respondidos via correio (Sattel et al, 2012) ou email (Gude e Hoffart 2008).…”
Section: Métodos E Medidas Utilizados No Follow-upunclassified
See 1 more Smart Citation